Education for Sustainability, Transformational Learning Time and the Individual <–> Collective Dialectic - VanWynsberghe, Rob (Frontiers in Education, 2022)
Conceptualizing individual actions in relation to our social institutions is a sociological truism. In the context of sustainability, powerful social institutions like education, are getting tested by the actions of ordinary individuals, including students. Like is so often the case, younger members of society are active in efforts to force open the black box of individual-collective change and disrupt the habit-forming power of social institutions. This paper details a case study of an education for sustainability graduate program in order to further theorize transformative learning in the relationships amongst individual action(s), collective change(s) and the border-like but permeable spaces that are in-between. It asks the practical question of the ways we might expansively and generatively work together in classroom to be the bridge between individual action and collective change.